Antioxidant, sound-absorbing and shock-absorbing MAX-phase or MAB-phase material and preparation method thereof

By designing the dense surface layer and porous internal structure of the MAX phase or MAB phase material, combined with the high -temperature sintering process, the existing materials are difficult to take into account the problem of multiple characteristics, and the multifunctional integration performance in high temperature environments.

CN119350033APending Publication Date: 2025-01-24XIAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411532658.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing MAX phase or MAB phase materials are difficult to take into account the multiple characteristics of oxidation resistance, ablation resistance, thermal shock resistance, sound absorption, heat insulation and shock absorption at high temperatures, especially in complex service environments.

Method used

The surface layer of the design material is the MAX phase or MAB phase of the dense structure. The internal is a porous structure. It combines the pre -pressure treatment of different particle size A raw materials and the high -temperature sintering process to achieve the multifunctional integration of the material.

Benefits of technology

It realizes excellent anti -oxidation, ablation and heat -resistant seismic characteristics in high temperature environments, and has good sound absorption, shock absorption and insulation performance, and meets multiple needs in the complex service environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350033A_ABST
    Figure CN119350033A_ABST
Patent Text Reader

Abstract

The invention discloses an antioxidant, sound-absorbing and shock-absorbing MAX-phase or MAB-phase material and a preparation method thereof, and belongs to the technical field of functional materials. According to the material disclosed by the invention, the surface layer of the material is an MAX phase or an MAB phase with a compact structure, so that the excellent characteristics of oxidation resistance, ablation resistance, thermal shock resistance and the like can be provided; the interior of the material is an MAX phase or an MAB phase of a porous structure, good sound absorption, shock absorption, heat insulation and other characteristics can be provided, by conducting structural design on the MAX phase or MAB phase material, integration of multiple functions is achieved, especially the properties of oxidation resistance, ablation resistance, thermal shock resistance, sound absorption, shock absorption, heat insulation and the like at the high temperature are achieved, and the material is suitable for large-scale popularization and application. And multiple demands in a complex service environment can be considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and in particular relates to an anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of aerospace, national defense and military fields, equipment hot end components, such as turbine blades, guide vanes, turbine discs, combustion chambers, tail nozzles, etc., are gradually facing more complex and harsh service environments. Therefore, higher requirements are placed on the high temperature performance of materials, especially the anti-oxidation and anti-ablation properties at high temperatures.

[0003] Traditional high-temperature alloy materials have been unable to meet the expected demand due to their poor oxidation resistance. For example, the oxidation resistance of molybdenum alloy, tantalum alloy, titanium alloy and iron alloy drops sharply at 400℃, 500℃, 600℃ and 650℃ respectively, and as the temperature rises, the degree of oxidation continues to increase, and the mechanical properties of the material also decreases, which has become the main obstacle to the application and development of high-temperature alloys to higher temperatures.

[0004] Al-containing MAX phase or MAB phase materials are a new type of ceramic material. Due to its unique hybrid bonding characteristics, it combines many excellent properties of metal and ceramic materials. For example, it exhibits good fracture toughness, good electrical and thermal conductivity under low temperature conditions, and has high strength, low expansion coefficient, excellent oxidation resistance and ablation resistance under high temperature conditions. Therefore, it has become an ideal high-temperature candidate material in the fields of aerospace, national defense and military.

[0005] However, the MAX phase or MAB phase materials synthesized at present are mainly single-structure types. In response to the high requirements of modern equipment for multiple properties, such as anti-oxidation, anti-ablation, thermal shock resistance, as well as sound absorption, heat insulation and shock absorption, these materials are still insufficient in terms of compatibility with multiple functions. Among them, the Chinese patent application with publication number CN101747075A discloses porous conductive MAX phase ceramics and their preparation methods and uses, and obtains MAX phase ceramics with through-pore structures by pressureless sintering, including Ti3SiC2, Ti3AlC2, and Ti2AlC. The porosity of the obtained ceramics is between 20% and 65%, and the open porosity is between 85% and 100%. Although this single porous structure design is conducive to heat insulation, it also aggravates the penetration of external corrosive gases, which reduces the anti-oxidation and anti-ablation properties of the material. In addition, a Chinese patent application with publication number CN110698204A discloses a method for preparing MAX phase ceramics, by ball-milling three or more MAX phase ceramic powders with a 211 structure with a certain proportion of Cr2AlC powder, and then hot-pressing and sintering at high temperature to obtain a MAX phase ceramic containing a large amount of high entropy 413 structure. This component optimization design solves the weaknesses of low strength and low hardness of ordinary MAX phase ceramics. However, the improvement of material strength / hardness often comes at the expense of its fracture toughness and machinability, and the dense structural material obtained by hot pressing and sintering is not conducive to the lightweighting of thermal structural parts.

[0006] It can be seen that it is difficult for single-structure MAX phase or MAB phase materials to take into account the multiple properties currently required, especially oxidation resistance, ablation resistance, thermal shock resistance, heat insulation, sound absorption and vibration reduction at high temperatures. Therefore, it is particularly important to achieve multifunctional integration in complex service environments through structural design of MAX phase or MAB phase materials. Summary of the invention

[0007] The purpose of the present invention is to provide an antioxidant, sound-absorbing and shock-absorbing MAX phase or MAB phase material and a preparation method thereof, so as to solve the technical problems that are difficult to take into account in the prior art in complex service environments, especially antioxidant, ablation resistance, thermal shock resistance, sound absorption, heat insulation and shock absorption in high temperature environments.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses an anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material. The surface layer of the material is a MAX phase or MAB phase with a dense structure, and the rest is a MAX phase or MAB phase with a porous structure. Furthermore, the MAX phase or MAB phase material is an Al-containing MAX phase or MAB phase.

[0009] The present invention also discloses a method for preparing the above-mentioned anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material, comprising the following steps: Mixing raw material M, raw material A with a particle size of 30 to 80 μm, raw material X or B, stearic acid and ethanol to obtain mixed powder Q1; Mixing raw material M, raw material A with a particle size of 0.2 to 5.0 μm, raw material X or B, stearic acid and ethanol to obtain a mixed powder Q2; The mixed powder Q1 is loaded into the bottom layer of the mold, and then the mixed powder Q2 is loaded into the upper layer of the mixed powder Q1, and a pre-pressing treatment is performed to obtain a precursor green body; The precursor green body is subjected to high temperature sintering treatment to obtain the oxidation-resistant and sound-absorbing and vibration-reducing MAX phase or MAB phase material.

[0010] Furthermore, in the mixed powder Q1 and the mixed powder Q2, the usage ratio of the M raw material, the A raw material, the X raw material and the ethanol is (1.0-4.0) mol%: (1.0-4.0) mol%: (1.0-3.0) mol%: (2-10) mL; In the mixed powder Q1 and the mixed powder Q2, 3-8 wt.% of stearic acid is added to the raw material powder; The usage ratio of the mixed powder Q1 and the mixed powder Q2 is (0.2-1.0): (2.5-5.0) wt.%.

[0011] Further, the M raw material includes hydrides, carbides, nitrides, or borides of titanium, chromium, molybdenum, iron, manganese, tungsten, niobium, zirconium, vanadium, and tantalum; the A raw material includes one or more of intermetallic compounds, carbides, nitrides, or borides of Al; the X raw material includes one or more of carbon-containing or nitrogen-containing compounds; and the B raw material includes one or more of boron-containing compounds.

[0012] Furthermore, the M raw material also includes single substances of titanium, chromium, molybdenum, iron, manganese, tungsten, niobium, zirconium, vanadium and tantalum; the A raw material also includes single substance of aluminum; the X raw material also includes single substance of carbon, and the B raw material also includes boron powder.

[0013] Furthermore, the mixing method is ball milling; the ball-to-material ratio of the ball milling is (1-5):1, the rotation speed is 100-400 rpm, and the time is 5-24 h; The ball milling process further includes drying treatment, wherein the drying temperature is 50-80° C. and the drying time is 8-24 hours.

[0014] Furthermore, the pressure of the pre-pressing treatment is 20-300 MPa.

[0015] Furthermore, the temperature of the high temperature sintering treatment is 1000-1800°C, and the holding time is 1-8 h; the high temperature sintering treatment is carried out in an inert atmosphere or under vacuum conditions; the vacuum satisfies ≤1.2×10 -3 Pa conditions.

[0016] Furthermore, the specific process of the high temperature sintering treatment is as follows: First, the temperature is raised to 300~400℃ and kept for 1~4 h, then raised to 600~700℃ and kept for 1~4 h, then raised to 800~900℃ and kept for 1~4 h, and finally raised to 1000~1800℃ and kept for 1~8 h. The heating rate during the whole process is less than 5℃ / min.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses an antioxidant, sound-absorbing and shock-reducing MAX phase or MAB phase material. The surface layer of the material is a densely structured MAX phase or MAB phase, which can provide excellent antioxidant, ablation-resistant and thermal shock-resistant properties; the interior of the material is a porous MAX phase or MAB phase, which can provide good sound absorption, shock reduction and heat insulation properties. The present invention achieves multi-functional integration by structurally designing the MAX phase or MAB phase material, especially antioxidant, ablation-resistant, thermal shock-resistant and sound absorption, shock reduction and heat insulation properties at high temperatures, and can take into account multiple needs in a complex service environment.

[0018] The present invention also discloses a method for preparing the above-mentioned antioxidant and sound-absorbing and shock-absorbing MAX phase or MAB phase material, which makes use of the different-scale pores remaining in the pre-pressing process of raw materials with different particle sizes A, and the solid-state partial diffusion pore formation caused by the Kirkendall effect during the solid-phase reaction sintering process, to achieve effective design of the MAX phase or MAB phase material structure, so that the prepared MAX phase or MAB phase material is compatible with multiple excellent properties; the material preparation process described in the present invention is simple and stable, and can realize large-scale and large-scale industrial production, which is convenient for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the cross-sectional structure of the MAX phase or MAB phase material for anti-oxidation and sound absorption and vibration reduction of the present invention. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0021] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0022] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0023] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0024] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0025] The present invention provides an anti-oxidation and sound-absorbing and shock-absorbing MAX phase or MAB phase material, wherein the MAX phase or MAB phase material refers to an Al-containing MAX phase or MAB phase, including but not limited to Ti2AlC, Cr2AlC, Zr2AlC, Hf2AlC, V2AlC, Nb2AlC, Ta2AlC, Ti3AlC2, V4AlC3, Mo2TiAlC2, Cr2AlB2, Cr4AlB4, Cr3AlB4, Cr4AlB6, Mn2AlB2, Fe2AlB2, MoAlB, WAlB, etc. The anti-oxidation and sound-absorbing and shock-absorbing MAX phase or MAB phase material has a surface layer of a densely structured MAX phase or MAB phase, which can provide excellent anti-oxidation, anti-ablation and thermal shock resistance properties; the rest of the MAX phase or MAB phase is a porous structure, which can provide good sound absorption, shock absorption and heat insulation properties.

[0026] The present invention also provides a method for preparing the above-mentioned anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material, comprising the following steps: S1, low-energy ball milling mixing: M and X raw materials or M and B raw materials are mixed with two A raw materials with particle sizes of 30-80 μm and 0.2-5.0 μm respectively in a certain molar ratio, dried and sieved to obtain mixed powders Q1 and Q2; S2, cold pressing: the prepared mixed powder Q1 is loaded into the bottom layer of the mold, and then the mixed powder Q2 is loaded into the upper layer of the mold, and pre-pressed to obtain a precursor green body; S3, high temperature solid phase reaction sintering: the obtained precursor green body is subjected to high temperature sintering above the MAX phase or MAB phase formation temperature to obtain the oxidation resistant and sound absorbing and vibration reducing MAX phase or MAB phase material.

[0027] Further, in S1, the low-energy ball milling mixing comprises the following steps: Select two kinds of raw materials A with particle sizes of 30-80 μm and 0.2-5.0 μm, weigh the raw materials M, A, X or M, A, B containing raw materials A with different particle sizes according to the element molar ratio of (1.0-4.0): (1.0-4.0): (1.0-3.0), and mix them with 3-8% stearic acid and 2-10 mL of anhydrous ethanol; Subsequently, the two mixed raw materials obtained above are placed in different ball mills with grinding balls at a ball-to-material ratio of (1-5):1, and are uniformly mixed in a planetary ball mill for 5-24 hours; the ball mill is made of agate, and the grinding balls are made of zirconia or agate; the ball mill rotates at a speed of 100-400 rpm, and operates in a forward and reverse direction alternately; After the ball milling is completed, take it out and place it in a vacuum drying oven with the temperature set at 50-80°C and the drying time set at 8-24 h. The two mixed raw materials after drying were sieved with the grinding balls, and a Taylor sieve was used in the process to separate the grinding balls to obtain two uniform mixed powders Q1 and Q2 containing raw material A with different particle sizes.

[0028] Further, in S2, the cold press forming comprises the following steps: The mixed powder Q1 prepared above is loaded into the bottom layer of the mold, and then the mixed powder Q2 is loaded into the upper layer of the mold, and the mixed powder is pressed into a green compact at a pressure of 20-300 MPa; Further, in S3, the high temperature solid phase reaction sintering comprises the following steps: The pre-pressed precursor green body is placed in a mold for high-temperature sintering. The mold is a mold known in the art and is not specifically limited in the present invention. The high-temperature sintering is performed without applying pressure, and an inert atmosphere is introduced during the process or under vacuum conditions (≤1.2×10 -3 Pa); the equipment used in the heating process includes but is not limited to a tube furnace, a muffle furnace, a box furnace, a hot press furnace, etc.; During the sintering process, a total of 4 heat preservation platforms are set up. First, the temperature is raised to 300-400°C and kept for 1-4 hours to promote the decomposition of stearic acid; then the temperature is raised to 600-700°C and kept for 1-4 hours to intensify the thermal diffusion of Al; then the temperature is raised to 800-900°C and kept for 1-4 hours to promote the transformation of the intermediate product into MAX phase or MAB phase; finally, the temperature is raised to 1000-1800°C and kept for 1-8 hours. The heating rate of the whole process is less than 5°C / min. After the sintering is completed, the furnace is cooled to obtain an anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material of the present invention.

[0029] The anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material of the present invention can be used for equipment skin and hot end component materials, such as turbine blades, guide vanes, turbine disks, combustion chambers, tail nozzles, etc.

[0030] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0031] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0032] Example 1 A method for preparing an oxidation-resistant and sound-absorbing and vibration-reducing Ti2AlC material comprises the following steps: Step 1: Titanium powder (Ti, purity 99.9%), carbon powder (C, purity 99.9%), and two kinds of aluminum powder (Al, purity 99.9%) with particle sizes of 30 μm and 0.2 μm were selected as raw materials. 191.48 g, 59.36 g, 24.02 g and 574.44 g, 178.08 g, 72.06 g of Ti, Al, and C raw materials containing Al with different particle sizes were weighed according to the element molar ratio of 2:1.1:1, and then the two mixed raw materials were mixed with 4% stearic acid and 6 mL of anhydrous ethanol; Then, the two mixed raw materials and grinding balls obtained above were placed in different ball mills according to a ball-to-material ratio of 5:1, and were uniformly mixed in a planetary ball mill for 10 h; the ball mill was made of agate, and the grinding balls were made of agate; the ball mill rotated at 400 rpm, and operated alternately in forward and reverse directions. After the ball milling mixing was completed, the mixture was taken out and placed in a vacuum drying oven with a set temperature of 80°C and a drying time of 24 h. The two mixed raw materials and grinding balls after drying were sieved, and a Taylor sieve was used in the process to separate the grinding balls to obtain two uniform mixed powders Q1 (Al particle size of 30 μm) and mixed powder Q2 (Al particle size of 0.2 μm) containing Al raw materials with different particle sizes. Step 2: The prepared mixed powder Q1 is loaded into the bottom layer of the cold pressing mold, and then the mixed powder Q2 is loaded into the upper layer of the cold pressing mold, and the mixed powder is pressed at a pressure of 160 MPa to obtain a precursor green body; Step 3: The pre-pressed precursor green body is placed into a graphite mold for high temperature sintering. During the process, the vacuum degree is maintained at 1.2×10 -3 Pa, set the sintering program, the sintering temperature has 4 insulation platforms, firstly raise the temperature to 360℃ and keep it for 2 h, then raise the temperature to 620℃ and keep it for 2 h, then raise the temperature to 850℃ and keep it for 2 h, finally raise the temperature to 1300℃ and keep it for 4 h. The heating rate in the whole process is less than 5℃ / min. After sintering, cool with the furnace to obtain the antioxidant and sound-absorbing and vibration-reducing Ti2AlC material composed of a dense surface structure and an internal porous structure of the present invention.

[0033] Example 2 A method for preparing an oxidation-resistant and sound-absorbing and vibration-reducing Cr2AlC material comprises the following steps: Step 1: Chromium powder (Cr, purity 99.9%), carbon powder (C, purity 99.9%), and two kinds of aluminum powder (Al, purity 99.9%) with particle sizes of 40 μm and 0.5 μm were selected as raw materials. 208 g, 64.75 g, 24.02 g of Cr, 624 g, 194.25 g, 72.06 g of C raw materials containing Al with different particle sizes were weighed according to the element molar ratio of 2:1.2:1, and then the two mixed raw materials were mixed with 5% stearic acid and 6 mL of anhydrous ethanol; Then, the two mixed raw materials and grinding balls obtained above were placed in different ball mills according to a ball-to-material ratio of 5:1, and were uniformly mixed in a planetary ball mill for 10 h; the ball mill was made of agate, and the grinding balls were made of agate; the ball mill rotated at 400 rpm, and operated alternately in forward and reverse directions. After the ball milling mixing was completed, the mixture was taken out and placed in a vacuum drying oven with a set temperature of 80 °C and a drying time of 24 h. The two mixed raw materials and grinding balls after drying were sieved, and a Taylor sieve was used in the process to separate the grinding balls to obtain two uniform mixed powders Q1 (Al particle size of 40 μm) and mixed powder Q2 (Al particle size of 0.5 μm) containing Al raw materials with different particle sizes. Step 2: The prepared mixed powder Q1 is loaded into the bottom layer of the cold pressing mold, and then the mixed powder Q2 is loaded into the upper layer of the cold pressing mold, and the mixed powder is pressed at a pressure of 160 MPa to obtain a precursor green body; Step 3: The pre-pressed precursor green body is placed into a graphite mold for high temperature sintering. During the process, the vacuum degree is maintained at 1.2×10 -3 Pa, set the sintering program, the sintering temperature has 4 insulation platforms, firstly, the temperature is raised to 360 ℃ and kept for 2 h, then the temperature is raised to 620 ℃ and kept for 2 h, then the temperature is raised to 850 ℃ and kept for 2 h, and finally the temperature is raised to 1250 ℃ and kept for 4 h. The heating rate in the whole process is less than 5 ℃ / min. After the sintering is completed, the furnace is cooled to obtain the antioxidant and sound-absorbing and vibration-reducing Cr2AlC material composed of a dense surface structure and an internal porous structure of the present invention.

[0034] Example 3 A method for preparing an oxidation-resistant and sound-absorbing and vibration-reducing Ti3AlC2 material comprises the following steps: Step 1: Titanium powder (Ti, purity 99.9%), carbon powder (C, purity 99.9%), and two kinds of aluminum powder (Al, purity 99.9%) with particle sizes of 50 μm and 0.8 μm were selected as raw materials. According to the element molar ratio of 3:1.3:2, 287.22 g, 59.36 g, 48.04 g of Ti, 574.44 g, 118.72 g, 96.08 g of C raw materials containing Al with different particle sizes were weighed respectively. Then, the two mixed raw materials were mixed with 5% stearic acid and 5 mL of anhydrous ethanol. Then, the two mixed raw materials and grinding balls obtained above were placed in different ball mills according to a ball-to-material ratio of 5:1, and were uniformly mixed in a planetary ball mill for 10 h; the ball mill was made of agate, and the grinding balls were made of agate; the ball mill rotated at 400 rpm, and operated alternately in forward and reverse directions. After the ball milling mixing was completed, the mixture was taken out and placed in a vacuum drying oven with a set temperature of 80°C and a drying time of 24 h. The two mixed raw materials and grinding balls after drying were sieved, and a Taylor sieve was used in the process to separate the grinding balls to obtain two uniform mixed powders Q1 (Al particle size of 50 μm) and mixed powder Q2 (Al particle size of 0.8 μm) containing Al raw materials with different particle sizes. Step 2: The prepared mixed powder Q1 is loaded into the bottom layer of the cold pressing mold, and then the mixed powder Q2 is loaded into the upper layer of the cold pressing mold, and the mixed powder is pressed at a pressure of 200 MPa to obtain a precursor green body; Step 3: The pre-pressed precursor green body is placed into a graphite mold for high temperature sintering. During the process, the vacuum degree is maintained at 1.2×10 -3 Pa, set the sintering program, the sintering temperature has 4 insulation platforms, firstly raise the temperature to 360℃ and keep it for 2 h, then raise the temperature to 620℃ and keep it for 2 h, then raise the temperature to 850℃ and keep it for 2 h, finally raise the temperature to 1500℃ and keep it for 4 h. The heating rate in the whole process is less than 5℃ / min. After sintering, cool with the furnace to obtain the antioxidant and sound-absorbing and vibration-reducing Ti3AlC2 material composed of a dense surface structure and an internal porous structure of the present invention.

[0035] Example 4 A method for preparing an anti-oxidation and sound-absorbing and vibration-reducing MoAlB material comprises the following steps: Step 1: Molybdenum powder (Mo, purity 99.9%), boron powder (B, purity 99.9%), and two kinds of aluminum powder (Al, purity 99.9%) with particle sizes of 60 μm and 1.0 μm were selected as raw materials. 191.88 g, 70.148 g, 21.62 g and 575.64 g, 210.44 g, 64.86 g of Mo, Al, and B raw materials containing Al with different particle sizes were weighed according to the element molar ratio of 1:1.3:1, and then the two mixed raw materials were mixed with 5% stearic acid and 5 mL of anhydrous ethanol; Then, the two mixed raw materials and grinding balls obtained above were placed in different ball mills according to a ball-to-material ratio of 5:1, and were uniformly mixed in a planetary ball mill for 10 h; the ball mill was made of agate, and the grinding balls were made of agate; the ball mill rotated at 400 rpm, and operated alternately in forward and reverse directions. After the ball milling mixing was completed, the mixture was taken out and placed in a vacuum drying oven with a set temperature of 80°C and a drying time of 24 h. The two mixed raw materials and grinding balls after drying were sieved, and a Taylor sieve was used in the process to separate the grinding balls to obtain two uniform mixed powders Q1 (Al particle size of 60 μm) and mixed powder Q2 (Al particle size of 1.0 μm) containing Al raw materials with different particle sizes. Step 2: The prepared mixed powder Q1 is loaded into the bottom layer of the cold pressing mold, and then the mixed powder Q2 is loaded into the upper layer of the cold pressing mold, and the mixed powder is pressed at a pressure of 200 MPa to obtain a precursor green body; Step 3: The pre-pressed precursor green body is placed into a graphite mold for high temperature sintering. During the process, the vacuum degree is maintained at 1.2×10 -3 Pa, set the sintering program, the sintering temperature has 4 insulation platforms, firstly raise the temperature to 360℃ and keep it for 2h, then raise the temperature to 620℃ and keep it for 2h, then raise the temperature to 850℃ and keep it for 2h, finally raise the temperature to 1200℃ and keep it for 4h, the heating rate in the whole process is less than 5℃ / min, after sintering, cool with the furnace, so as to obtain the antioxidant and sound-absorbing and vibration-reducing MoAlB material composed of a dense surface structure and an internal porous structure of the present invention.

[0036] Example 5 A method for preparing an anti-oxidation and sound-absorbing and vibration-reducing WAlB material comprises the following steps: Step 1: Tungsten powder (W, purity 99.9%), boron powder (B, purity 99.9%), and two kinds of aluminum powder (Al, purity 99.9%) with particle sizes of 70 μm and 3.0 μm were selected as raw materials. 183.8 g, 35.074 g, 10.81 g of W, 551.4 g, 105.22 g, and 21.62 g of B raw materials containing Al with different particle sizes were weighed according to the element molar ratio of 1:1.3:1, and then the two mixed raw materials were mixed with 5% stearic acid and 5 mL of anhydrous ethanol; Then, the two mixed raw materials and grinding balls obtained above were placed in different ball mills according to a ball-to-material ratio of 5:1, and were uniformly mixed in a planetary ball mill for 10 h; the ball mill was made of agate, and the grinding balls were made of agate; the ball mill rotated at 400 rpm, and operated alternately in forward and reverse directions. After the ball milling mixing was completed, the mixture was taken out and placed in a vacuum drying oven with a set temperature of 80°C and a drying time of 24 h. The two mixed raw materials and grinding balls after drying were sieved, and a Taylor sieve was used in the process to separate the grinding balls to obtain two uniform mixed powders Q1 (Al particle size of 70 μm) and mixed powder Q2 (Al particle size of 3.0 μm) containing Al raw materials with different particle sizes. Step 2: The prepared mixed powder Q1 is loaded into the bottom layer of the cold pressing mold, and then the mixed powder Q2 is loaded into the upper layer of the cold pressing mold, and the mixed powder is pressed at a pressure of 200 MPa to obtain a precursor green body; Step 3: The pre-pressed precursor green body is placed into a graphite mold for high temperature sintering. During the process, the vacuum degree is maintained at 1.2×10 -3 Pa, set the sintering program, the sintering temperature has 4 insulation platforms, firstly raise the temperature to 360℃ and keep it for 2h, then raise the temperature to 620℃ and keep it for 2h, then raise the temperature to 850℃ and keep it for 2h, finally raise the temperature to 1500℃ and keep it for 4h, the heating rate in the whole process is less than 5℃ / min, after sintering, cool with the furnace, and obtain the antioxidant and sound-absorbing and vibration-reducing WAlB material composed of a dense surface structure and an internal porous structure of the present invention.

[0037] Example 6 A method for preparing an anti-oxidation and sound-absorbing and vibration-reducing Cr2AlB2 material comprises the following steps: Step 1: Chromium powder (Cr, purity 99.9%), boron powder (B, purity 99.9%), and two kinds of aluminum powder (Al, purity 99.9%) with particle sizes of 80 μm and 5.0 μm were selected as raw materials. 208 g, 70.148 g, 43.24 g of Cr, 624 g, 210.444 g, 129.72 g of B raw materials containing Al with different particle sizes were weighed according to the element molar ratio of 2:1.3:2, and then the two mixed raw materials were mixed with 5% stearic acid and 5 mL of anhydrous ethanol; Then, the two mixed raw materials and grinding balls obtained above were placed in different ball mills according to a ball-to-material ratio of 5:1, and were uniformly mixed in a planetary ball mill for 10 h; the ball mill was made of agate, and the grinding balls were made of agate; the ball mill rotated at 400 rpm, and operated alternately in forward and reverse directions. After the ball milling mixing was completed, the mixture was taken out and placed in a vacuum drying oven with a set temperature of 80°C and a drying time of 24 h. The two mixed raw materials and grinding balls after drying were sieved, and a Taylor sieve was used in the process to separate the grinding balls to obtain two uniform mixed powders Q1 (Al particle size of 80 μm) and mixed powder Q2 (Al particle size of 5.0 μm) containing Al raw materials with different particle sizes. Step 2: The prepared mixed powder Q1 is loaded into the bottom layer of the cold pressing mold, and then the mixed powder Q2 is loaded into the upper layer of the cold pressing mold, and the mixed powder is pressed at a pressure of 200 MPa to obtain a precursor green body; Step 3: The pre-pressed precursor green body is placed into a graphite mold for high temperature sintering. During the process, the vacuum degree is maintained at 1.2×10 -3 Pa, set the sintering program, the sintering temperature has 4 insulation platforms, firstly raise the temperature to 360℃ and keep it for 2h, then raise the temperature to 620℃ and keep it for 2h, then raise the temperature to 850℃ and keep it for 2h, finally raise the temperature to 1100℃ and keep it for 4h. The heating rate in the whole process is less than 5℃ / min. After sintering, cool with the furnace to obtain the antioxidant and sound-absorbing and vibration-damping Cr2AlB2 material composed of a dense surface structure and an internal porous structure of the present invention.

[0038] The cross-sectional schematic diagram of the MAX phase or MAB phase material with both oxidation resistance and sound absorption and vibration reduction prepared by the present invention is as follows: Figure 1 As shown, it can be seen that the surface layer of the material is a dense structure MAX phase or MAB phase, and the rest is a porous structure MAX phase or MAB phase; wherein the MAX phase or MAB phase material is an Al-containing MAX phase or MAB phase; the present invention achieves excellent anti-oxidation, anti-ablation, anti-thermal shock and good sound absorption, shock absorption and heat insulation properties by designing the structure of the MAX phase or MAB phase material, which can meet the multiple needs of equipment in a complex service environment. The anti-oxidation and sound absorption and shock absorption MAX phase or MAB phase material of the present invention has a simple and stable preparation process, can realize large-scale and large-scale industrial production, and is easy to promote and apply.

[0039] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. An anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material, characterized in that: The surface layer of the material is a MAX phase or a MAB phase with a dense structure, and the rest of the material is a MAX phase or a MAB phase with a porous structure.

2. The anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material according to claim 1, characterized in that: The MAX phase or MAB phase material is an Al-containing MAX phase or MAB phase.

3. The method for preparing the MAX phase or MAB phase material having both oxidation resistance and sound absorption and vibration reduction according to claim 1 or 2, characterized in that: The following steps are involved: Mixing raw material M, raw material A with a particle size of 30 to 80 μm, raw material X or B, stearic acid and ethanol to obtain mixed powder Q1; Mixing raw material M, raw material A with a particle size of 0.2 to 5.0 μm, raw material X or B, stearic acid and ethanol to obtain a mixed powder Q2; The mixed powder Q1 is loaded into the bottom layer of the mold, and then the mixed powder Q2 is loaded into the upper layer of the mixed powder Q1, and a pre-pressing treatment is performed to obtain a precursor green body; The precursor green body is subjected to high temperature sintering treatment to obtain the oxidation-resistant and sound-absorbing and vibration-reducing MAX phase or MAB phase material.

4. The method for preparing an anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material according to claim 3, characterized in that: In the mixed powders Q1 and Q2, the usage ratios of the M raw material, the A raw material, the X raw material and ethanol are all (1.0-4.0) mol%: (1.0-4.0) mol%: (1.0-3.0) mol%: (2-10) mL; In the mixed powder Q1 and the mixed powder Q2, 3-8 wt.% of stearic acid is added to the raw material powder; The usage ratio of the mixed powder Q1 and the mixed powder Q2 is (0.2-1.0): (2.5-5.0) wt.%.

5. The method for preparing an anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material according to claim 3, characterized in that: The M raw material includes hydrides, carbides, nitrides, or borides of titanium, chromium, molybdenum, iron, manganese, tungsten, niobium, zirconium, vanadium, and tantalum; the A raw material includes one or more of intermetallic compounds, carbides, nitrides, or borides of Al; the X raw material includes one or more of carbon-containing or nitrogen-containing compounds; and the B raw material includes one or more of boron-containing compounds.

6. The method for preparing an anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material according to claim 5, characterized in that: The M raw material also includes simple substances of titanium, chromium, molybdenum, iron, manganese, tungsten, niobium, zirconium, vanadium and tantalum; the A raw material also includes simple substance of aluminum; the X raw material also includes simple substance of carbon; and the B raw material also includes boron powder.

7. The method for preparing an anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material according to claim 3, characterized in that: The mixing method is ball milling; the ball-to-material ratio of the ball milling is (1-5):1, the rotation speed is 100-400 rpm, and the time is 5-24 h; The ball milling process further includes drying treatment, wherein the drying temperature is 50-80° C. and the drying time is 8-24 h.

8. The method for preparing an anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material according to claim 3, characterized in that: The pre-pressing treatment pressure is 20-300 MPa.

9. The method for preparing an anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material according to claim 3, characterized in that: The temperature of the high temperature sintering treatment is 1000~1800℃, and the holding time is 1~8 hours; the high temperature sintering treatment is carried out in an inert atmosphere or vacuum conditions; the vacuum meets ≤1.2×10 -3 Pa conditions.

10. The method for preparing an anti-oxidation and sound-absorbing and vibration-reducing MAX phase or MAB phase material according to claim 9, characterized in that: The specific processing process of the high temperature sintering treatment is: First, the temperature is raised to 300~400℃ and kept for 1~4 h, then raised to 600~700℃ and kept for 1~4 h, then raised to 800~900℃ and kept for 1~4 h, and finally raised to 1000~1800℃ and kept for 1~8 h. The heating rate during the whole process is less than 5℃ / min.

Citation Information

Patent Citations

  • Porous conductive MAX phase ceramics and preparation method and use thereof

    CN101747075A

  • Preparation method of MAX phase ceramics

    CN110698204A

  • Binary doped gradient porous ultrahigh-temperature ceramic heat-insulating pressure-resistant wear-resistant coating and preparation method thereof

    CN117263712A

  • Sintered porous material and filter element using same

    WO2015000387A1